Environmental Study of Groundwater Quality of Selected Wells in Al-Zubair, Southern Iraq and their Uses - Al-khafaji, Raad; Amir, Fatma Abdel; Cheachan, Battol (Iraqi Journal of Science, 2023)
Twenty-five groundwater samples from the Al-Zubair area, southern Iraq, were analyzed for physical and chemical variables. The study showed that the groundwater is of acidic type and in it tends towards light alkalinity. Both electrical conductivity and the total dissolved solids showed increased concentrations of sodium, calcium, magnesium, potassium and sulfate, chloride, bicarbonate, and nitrate. The hydrochemical formula for most groundwater wells are (Ca-Cl), (Ca-SO4), (Mg-SO4), and (Na-Cl) type due to the high concentrations of these ions in the water., it was found that this water is not suitable for human drinking. Due to its high salinity compared to the requirements of international standard and Iraqi standardstandards, while it is suitable for drinking animal's construction purposes, it has not exceeded the permissible limits. Also, it has been found that this water is not suitable for industrial and irrigation purposes, where it is possible to grow crops that tolerate high salinity